The Branch and Cut Method for Solving Capacitated Vehicle Routing Problem (CVRP) Model of LPG Gas Distribution Routes: - - Evi Yuliza; F.M Puspita (Science and Technology Indonesia, 2019)
Capacitated Vehicle Routing Problem (CVRP) is a problem that discusses how to choose several routes that must be passed by a number of transport vehicles in the process of distributing goods that combine customer demand with regard to transport capacity. CVRP designs an optimal delivery route where each vehicle only takes one route, each vehicle has the same characteristics, each customer has a request and there is only one depot. In this paper, two CVRP models were formulated. Formulation of the first CVRP model without regard to vehicle loads and vehicles returned to the depot. The second CVRP model formulation takes into account the vehicle load and the vehicle does not return to the depot. Determination of LPG gas distribution routes is completed using the Branch and Cut method.